Incidence of malignancy in patients treated for antineutrophil cytoplasm antibody-associated vasculitis: follow-up data from European Vasculitis Study Group clinical trials. Issue 8 (25th May 2011) - Heijl, C; Harper, L; Flossmann, O; Stücker, I; Scott, DGI; Watts, R A; Höglund, P; Westman, K; Mahr, A; ,
Abstract : Objectives: Because standard immunosuppressive treatment for antineutrophil cytoplasm antibody-associated vasculitis (AAV) (granulomatosis with polyangiitis (Wegener's) (GPA) and microscopic polyangiitis (MPA)) has been associated with a significant risk of developing cancer, the cancer incidence of treated AAV patients was assessed. Methods: This analysis concerned 535 patients with newly diagnosed AAV from 15 countries who had been enrolled between 1995 and 2002 in four European clinical trials. Over the period 2004–7, study participants' follow-up events were updated, including cancers diagnosed. Age, sex and area-standardised incidence ratios (SIR) and their 95% CI were calculated by linkage to five national cancer databases. Results: During the 2650 person-years' observation period, 50 cancers were diagnosed in 46 patients. SIR (95% CI) were 1.58 (1.17 to 2.08) for cancers at all sites, 1.30 (0.90 to 1.80) for cancers at all sites excluding non-melanoma skin cancer (NMSC), 2.41 (0.66 to 6.17) for bladder cancer, 3.23 (0.39 to 11.65) for leukaemia, 1.11 (0.03 to 6.19) for lymphoma and 2.78 (1.56 to 4.59) for NMSC. Subgroup SIR for cancers at all sites were 1.92 (1.31 to 2.71) for GPA and 1.20 (0.71 to 1.89) for MPA. Conclusions: Cancer rates for AAV patients treated with conventional immunosuppressive therapy exceeded those expected for the general population. This cancer excess was largely driven by an increased incidence of NMSC. The smaller cancer risk magnitude in this cohort, compared with previous studies, might reflect less extensive use of cyclophosphamide in current treatment protocols. Longer follow-up data are warranted to appraise the risk of developing cancers later during the course of AAV.